THE EFFECT OF WORKLOAD AND COMPENSATION ON EMPLOYEE PERFORMANCE AT THE MEULABOH BRANCH OF BPJS KETENAGKERJAAN WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Siti Hajar; Nur Fajri; Putri Ridhotul Uliyah (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the influence of workload and compensation on employee performance at the Meulaboh Branch of BPJS Ketenagakerjaan, with job satisfaction as an intervening variable. A descriptive quantitative approach was used, with data collected through questionnaires and interviews from 17 respondents, consisting of BPJS employees. Data analysis conducted using multiple linear regression with the help of SPSS software and Path analysis. The results of the study indicate that accountability in management has a significant effect on Job Satisfaction. Workload affects employee performance with a significance value of variable X1 is 0.044, Compensation has a significant effect on employee performance, Analysis of X1 against Z: from the analysis obtained the significance value of variable X1 is 0.033, so it can be concluded that workload (X1) has a direct effect on job satisfaction (Z). Compensation against job satisfaction: from the analysis obtained the significance value of variable X2 is 0.034, so it can be concluded that Compensation (X2) has a direct effect on job satisfaction (Z). . Analysis of Y against Z: from the analysis obtained the significance value of variable Y is 0.049, so it can be concluded that employee performance (Y) has a direct effect on job satisfaction (Z). The direct effect of Y on Z has a direct effect of 0.143, and the indirect effect of X1 through Y on Z is 0.153.